The IL-17 pathway as a target in giant cell arteritis - Zeisbrich, Markus; Thiel, Jens; Venhoff, Nils (Frontiers in Immunology, 2024)
The network of IL-17 cytokines is considered a key component of autoimmune and inflammatory processes. Blocking IL-17 showed great success in psoriasis as well as psoriatic arthritis, and in patients with axial spondyloarthritis. Secukinumab is one of the approved IL-17A inhibitors for these diseases and is now routinely used. In giant cell arteritis, a large vessel vasculitis, there is accumulating evidence for a pathogenic role of IL-17 and Th17 cells, which are part of the CD4+ T-cell subset. Giant cell arteritis occurs in individuals over 50 years of age and many have relative contraindications to glucocorticoid therapy, which today still represents the mainstay therapy. Despite the approval of tocilizumab, which targets the IL-6 receptor, a high demand for glucocorticoid-sparing agents remains that combine the effective suppression of the acute inflammation observed in giant cell arteritis with a safety profile that matches the needs of an older patient population. The first results from a phase II proof-of-principle study (TitAIN) support an optimistic outlook on a potential new treatment option with secukinumab in giant cell arteritis.